Development of Digital Teaching Materials for Indonesian Phonetics with Sound Association Design for Basic Level BIPA Arabic Learners - Yoviyani, Salis Hilda; Mulyati, Yeti; Sastromiharjo, Andoyo; Halimah, Halimah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This research aims to develop digital teaching materials for Indonesian phonetics designed with sound association to support basic-level BIPA learners. This research method used research and development with the 4-D model, which consists of Define, Design, Develop, and Disseminate stages. The research instruments included pronunciation ability tests, learner needs questionnaires, BIPA teacher interview instruments, and validation sheets from experts and practitioners. The data analysis techniques used were qualitative and quantitative methods and Gregory's validity test with validity assessment criteria using the Likert Scale 1-4. The validation results indicated that the materials were "feasible" with some necessary revisions. After making the suggested revisions, the revised materials were piloted with basic-level BIPA learners. Feedback from these learners rated the materials as "very feasible", indicating a positive reception. The final product is a digital flipbook equipped with audio pronunciation guides and illustrations that can be accessed online. This format provides a flexible and engaging alternative for improving Indonesian pronunciation for Arabic-speaking BIPA learners, making it a valuable addition to the available teaching resources.